Quantum safety : the new approach to risk management for the complex workplace - Stretton, Paul (Productivity Press, 2022)
Quantum Safety is the most comprehensive review of Health & Safety in half a century. Most organizational approaches to Health & Safety are based on the methodology developed during the 1970s, and despite the workplace changing beyond recognition since that time, these approaches have remained untouched. Quantum Safety will develop a new understanding fit for the modern workplace. Quantum Safety is an approach that is part of the ⁰́₈"new view" debate. There have been a number of other new approaches to Health & Safety in recent years, and while all have merit and improve understanding to help create the optimal, safe working environment, they have failed to significantly create the change desired. These approaches are often flawed at the philosophical or conceptual level or propose a solution without a pathway to implement the principles in safety critical environments. Quantum Safety is founded on a wholesale critical analysis of the conceptual foundations of Health & Safety before translating the revised principles into a tangible methodology. Central to the development of Quantum Safety is the application of Complexity Science. The traditional approach to Health & Safety is considered to be Newtonian -- It uses linear models and deterministic analysis. Quantum Safety, due to the full consideration of Complexity Science, introduces multidimensional models and develops analysis based on probabilities. Crucially, this does not render Newtonian methodologies as worthless -- In the same manner that Newtonian Physics was able to take mankind to the moon, but required the Quantum understanding within computers to make it possible, Quantum Safety provides the mechanisms to complete organizations safety based journeys. The new mechanisms are fully developed for the reader at both macro and micro levels. How an organization measures safety and what it values is reset and reexamined. How we investigate adverse events and the consequential actions taken with employees to develop a true Just Culture within a high performing culture are also completely revised. Essentially, Quantum Safety creates a pathway for understanding Health & Safety in the complex modern world. To achieve that, new models are introduced to replace the dated, simple tools and a new language developed to communicate this powerful model. It will help propel an organization from considering safety within a concept of industrialized failure avoidance to valuing safety as an integrated aspect of high performance.